An updated animal model capturing both the cognitive and emotional features of post-traumatic stress disorder (PTSD) - Berardi, Andrea; Trezza, Viviana; Palmery, Maura; Trabace, Luigia; Cuomo, Vincenzo; Campolongo, Patrizia (Frontiers in Behavioral Neuroscience, 2014)
The new-released Diagnostic and Statistical Manual of Mental Disorders (DSM-5) defines post-traumatic stress disorder (PTSD) as a “trauma and stressor-related disorder”. PTSD pathogenesis relies on paradoxical changes of emotional memory processing induced by the trauma exposure and associated with emotional dysfunction. Several animal models of PTSD have been validated and are currently used. Each one mimics a particular subset of the disorder with particular emphasis, mainly driven by the past classification of PTSD in the DSM-4, on the emotional features. In view of the recent update in the DSM-5, our aim was to develop, by using well-validated paradigms, a modified model of PTSD able to mimic at the same time both the cognitive and emotional features of the disease. We exposed male rats to either a piece of worn cat collar or to a series of inescapable footshocks paired with a PTSD risk factor, i.e. social isolation. Animals were subsequently re-exposed to the conditioned contexts at different time intervals in order to test memory retention for the stressors. In addition, footshock-exposed rats were tested in the elevated-plus-maze and social interaction tests. We found that rats exposed to a cat collar exhibited an acute fear response that did not lead to enduring memory retention. Conversely, footshock-exposed rats expressed a successful retention of the stressful experience at 1, 7, 14, 21 and 56 post-exposure days. Footshock-exposed rats displayed an anxious behavioral profile in the social interaction test and a significantly reduced locomotor activity in the elevated-plus-maze test. These dysfunctions were not observed when animals were socially housed, thus highlighting a social buffer effect in the development of the pathology. Our results underline the good validity of a footshock-based paradigm paired with social isolation as a PTSD animal model, able to mimic at the same time both some of the enduring cognitive and emotional facets of the pathology.